The 5-minute consult : clinical companion to women's health - McGarry, Kelly A.; Tong, Iris L. (5-minute consult, 2013)
"The 5-Minute Consult Clinical Companion to Women's Health is a quick-reference guide to the diagnosis and management of symptoms and disorders that commonly occur in women. Written by both primary care physicians and obstetrician-gynecologists, the book covers disorders that are unique to women, occur disproportionately in women, or have a different clinical presentation, course, and/or prognosis in women. The contributors present practical, up-to-date, evidence-based information in a format designed for rapid consultation"--Provided by publisher.